Implementasi Metode Secure Hash Algorithm-1 Untuk Mendeteksi Keaslian File Dokumen - Dermawan Lumban Toruan; Rivalri Kristianto Hondro (Bulletin of Computer Science Research, 2021)
Document file is a means of transforming information from one person to another or from a group of other groups. The development of computerized technology has increased greatly. Document files are very vulnerable to fraud, interception and data theft by irresponsible parties. For the sake of maintaining the security of document files can be done by using cryptographic techniques. Cryptography is the science of maintaining data security. Cryptography is a data security method that can be used to maintain data authenticity, data confidentiality, and data transmission authenticity. SHA stands for Secure Hash Algorithm, a standard hash function published by NIST (National Institute of Standards and Technology), (NIST, 1995a). This research will use the SHA-1 method to secure the authenticity of document files, document confidentiality, document integrity, and document authentication. This study describes the security process to detect the authenticity of document files using the SHA-1 method in the form of detection so that confidential documents sent via public telecommunications cannot be changed or modified by unauthorized persons or unauthorized persons. This is done as an effort to minimize acts of fraud, hoaxes, or misuse of document files.